Self-development guidance for elementary-level orphanage children - Supraha, Wido; Herawati, Siti (TAWAZUN: Jurnal Pendidikan Islam, 2023)
This study aims to examine the effect of life skills guidance based on Islamic religious values on the self-development of foster children at the H. Haryono Mukana Orphanage. The research method used is qualitative research with a naturalistic inquiry approach, producing descriptive data in the form of written and spoken words and observable behaviour. Caregivers at the orphanage have an important role in providing physical, mental, social, and skills guidance to foster children. This life skills guidance is carried out through trainings that aim to provide skills to foster children so that they can be independent and successful outside the orphanage. It is hoped that this research can provide a deeper understanding of the effectiveness of life skills guidance based on Islamic religious values in shaping the self-development of foster children in orphanages, as well as contribute to improving their welfare and happiness in the future. Abstrak Penelitian ini bertujuan untuk mengkaji pengaruh bimbingan kecakapan hidup berbasis nilai-nilai agama Islam terhadap pengembangan diri anak asuh di Panti Asuhan H. Haryono Mukana. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan inkuiri naturalistik, menghasilkan data deskriptif berupa kata-kata tertulis dan lisan serta perilaku yang dapat diamati. Pengasuh di panti asuhan memiliki peran penting dalam memberikan bimbingan fisik, mental, sosial, dan keterampilan kepada anak asuh. Bimbingan kecakapan hidup ini dilakukan melalui pelatihan-pelatihan yang bertujuan untuk memberikan keterampilan kepada anak asuh agar dapat mandiri dan sukses di luar panti asuhan. Diharapkan penelitian ini dapat memberikan pemahaman lebih dalam tentang efektivitas bimbingan kecakapan hidup berbasis nilai-nilai agama Islam dalam membentuk pengembangan diri anak asuh di panti asuhan, serta memberikan kontribusi dalam meningkatkan kesejahteraan dan kebahagiaan mereka di masa depan.